2019
DOI: 10.4236/ojd.2019.81002
|View full text |Cite
|
Sign up to set email alerts
|

Functional Change of Brain Serotonergic Activity and Free Tryptophan in the Plasma of Depressed Women

Abstract: The main objective was to show the decrement of serotoninergic brain activity in depressed women, through the analyses of the slope amplitude of N1/P2 components of the auditory-evoked potentials (AEP), and the measurement of the L-tryptophan free fraction in plasma (FFT). This cross-sectional study was carried out in 60 women, 30 depressed and 30 normal controls. Both groups were measured FFT, glucose, and neutral amino acids (NAA) levels; besides performing AEP to analyses the N1/P2 slope amplitude. It was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…By analyzing the slope amplitude of N1/P2 components of auditory evoked potentials and the determination of Ltryptophan free fraction in plasma, it was found that the brain activity of serum neurosin and L-tryptophan free fraction decreased in women with depression (Vázquez-Estupiñan et al, 2019). After ovariectomy in female mice, it was found that FIGURE 2 | Mechanism underlying metabolism related depression.…”
Section: Neurotransmittersmentioning
confidence: 99%
See 1 more Smart Citation
“…By analyzing the slope amplitude of N1/P2 components of auditory evoked potentials and the determination of Ltryptophan free fraction in plasma, it was found that the brain activity of serum neurosin and L-tryptophan free fraction decreased in women with depression (Vázquez-Estupiñan et al, 2019). After ovariectomy in female mice, it was found that FIGURE 2 | Mechanism underlying metabolism related depression.…”
Section: Neurotransmittersmentioning
confidence: 99%
“…By analyzing the slope amplitude of N1/P2 components of auditory evoked potentials and the determination of L -tryptophan free fraction in plasma, it was found that the brain activity of serum neurosin and L -tryptophan free fraction decreased in women with depression ( Vázquez-Estupiñan et al, 2019 ). After ovariectomy in female mice, it was found that while estrogen decreased, the expression of IL-1β and IL-18, NLRP3 and the level of inflammatory cytokines such as active caspase-1 in the hippocampus of female mice increased significantly.…”
Section: The Underlying Mechanism Of Depressionmentioning
confidence: 99%